Determinants of Swiss firms' R&D activities at foreign locations: An empirical analysis based on firm-level data - Spyros Arvanitis; Heinz Hollenstein (ETH Zurich, KOF Swiss Economic Institute, 2006)
Using the OLI paradigm as theoretical framework, we explain econometrically why a firm invests in foreign R&D (model A), and, if it does, which factors determine the level of foreign R&D expenditures (model B). It turns out that the pattern of explanation is quite similar for both types of decisions. In both cases, O- and I-advantages are the main drivers of foreign R&D, whereas L-disadvantages of the Swiss location do not play any role. A descriptive analysis of a series of motives of Swiss firms for performing R&D abroad shows that market-seeking is the most important motive. Knowledge-seeking and (human) resource-seeking are of intermediate importance as motives of foreign R&D, whereas efficiency-seeking objectives are hardly relevant. These results are fully in line with those of the econometric modelling. The findings of both approaches imply that foreign and domestic R&D are complements rather than substitutes. Asset exploiting is more prevalent as a strategy of foreign R&D than asset augmenting.
Keywords: O30; 330; Foreign R&D; Determinants of foreign R&D; Motives of foreign R&D; OLI paradigm; Asset augmenting; Asset exploiting; Auslandsniederlassung; Direktinvestition; Industrielle Forschung; Schweiz